Przemiany formy graficznej książki dziecięco-młodzieżowej w ii połowie xx wieku na przykładzie wybranych publikacji Ewy Nowackiej - Chylak, Justyna (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The aim of the article is to analyze the changes in graphic design of the children and the youth’s books on the Polish publishing market during the last decades. Two periods can be distinguished here. The first one before 1989, when Polish publishing market was monopolized, but it really took care of the book`s graphic design (a high level of the Polish School of Illustration). Afterwards, many of the new publishers only took care of the book’s cover which is crucial to its success. The author presents this issue by giving the examples from Ewa Nowacka’s writings – the writer who has been publishing her books since 1967. The article is supplemented with information about Ewa Nowacka`s biography and her literary, review and journalist output.